The Influence of Hedonistic Lifestyle and Financial Self-Efficacy on the Level of Financial Literacy in Students of SMA N 1 Sunggal - Aulia Beywanda Idris; Ramadhan Harahap; Noni Ardian (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of a hedonistic lifestyle and financial self-efficacy on the level of financial literacy among students of SMA N 1 Sunggal. The type of research used is quantitative research with a conclusive approach that aims to obtain conclusions based on the objectives and research problems. The population in this study were students of SMA N 1 Sunggal with a sample of 50 respondents found through a simple random sampling technique. Data were collected using an online questionnaire compiled with a Likert scale. The data analysis technique used was multiple linear regression analysis to determine the effect of independent variables on the dependent variable. The results showed that the instruments used met the requirements of validity and reliability. In addition, the classical assumption test showed that the data were normally distributed with a significance value of 0.200 in the Kolmogorov-Smirnov test. The research findings indicate that a hedonistic lifestyle and financial self-efficacy simultaneously influence students' financial literacy levels. Strong financial self-efficacy helps students manage their finances better, while a hedonistic lifestyle is a factor that needs to be watched out for because of the tendency to prioritize pleasure.